“What do future educational leaders know about gender?”: A feminist content analysis - Debora Nelli (Adult Education Research Conference, 2009)
The educational access, opportunity and experience of students and educators in U.S. educational institutions is influenced and often limited by their gender. Gender discrimination impacts the academic, emotional, vocational and economic lives of both students and educators. The Glass Ceiling Commission sponsored by the U.S. Department of Labor determined key factors in the amelioration of institutional gender discrimination were the beliefs, values and commitments of the institution’s leaders (U.S. Dept of Labor, 1995). The pivotal role educational leaders play in either reproducing or disrupting institutional gender inequity makes it essential to examine cultural artifacts for insights into the expressed and implied values, beliefs and commitments of future educational leaders regarding gender issues.